To solve the problem, let's define two variables:
Let \( x = \) the cost of the first textbook.
Let \( y = \) the cost of the second textbook.
Now we can set up the equations based on the information provided:
-
The total cost of the two textbooks: \[ x + y = 65 \quad \text{(Equation 1)} \]
-
The difference in price between the two books: \[ x - y = 9 \quad \text{(Equation 2)} \]
Now we can solve the system of equations.
Step 1: Solve Equation 2 for \( x \)
From Equation 2: \[ x = y + 9 \]
Step 2: Substitute \( x \) in Equation 1
Substituting \( x \) in Equation 1: \[ (y + 9) + y = 65 \]
Combine the \( y \) terms: \[ 2y + 9 = 65 \]
Step 3: Solve for \( y \)
Subtract 9 from both sides: \[ 2y = 56 \] Divide by 2: \[ y = 28 \]
Step 4: Find \( x \)
Now substitute \( y \) back into the equation for \( x \): \[ x = y + 9 = 28 + 9 = 37 \]
Conclusion
The costs of the textbooks are:
- The first textbook cost \( x = 37 \).
- The second textbook cost \( y = 28 \).
Thus, the final answer is:
- Let \( x = 37 \)
- Let \( y = 28 \)